2017
DOI: 10.1038/s41467-017-02340-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP elicits DORN1-mediated RBOHD phosphorylation to regulate stomatal aperture

Abstract: In addition to acting as a cellular energy source, ATP can also act as a damage-associated molecular pattern in both animals and plants. Stomata are leaf pores that control gas exchange and, therefore, impact critical functions such as photosynthesis, drought tolerance, and also are the preferred entry point for pathogens. Here we show the addition of ATP leads to the rapid closure of leaf stomata and enhanced resistance to the bacterial pathogen Psuedomonas syringae. This response is mediated by ATP recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
202
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(229 citation statements)
references
References 67 publications
1
202
0
Order By: Relevance
“…In contrast to ABA and JA, which were required for stomatal closure in local and systemic leaves, suppression of SA biosynthesis in the SA induction deficient 2 ( sid2 ) mutant only affected stomatal responses in systemic leaves (Fig. k), potentially suggesting that systemic stomatal responses to light stress could be associated with pathogen‐induced stomatal closure pathways (Chen et al ., ; Devireddy et al ., ; David et al ., ; Kollist et al ., ). The findings presented in Fig.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to ABA and JA, which were required for stomatal closure in local and systemic leaves, suppression of SA biosynthesis in the SA induction deficient 2 ( sid2 ) mutant only affected stomatal responses in systemic leaves (Fig. k), potentially suggesting that systemic stomatal responses to light stress could be associated with pathogen‐induced stomatal closure pathways (Chen et al ., ; Devireddy et al ., ; David et al ., ; Kollist et al ., ). The findings presented in Fig.…”
mentioning
confidence: 97%
“…Rapid alterations in stomatal aperture were previously shown to regulate leaf temperature, rates of CO 2 exchange, water vapor loss and responses to pathogen infection (Melotto et al ., ; Vahisalu et al ., ; Raven, ; Guzel Deger et al ., ; Chen et al ., ; Devireddy et al ., ; Yoshida & Fernie, ; Zhang et al ., ; Kollist et al ., ). Here, it is shown that rapid alterations in stomatal aperture (opening or closing) induced by different environmental stimuli in a local leaf trigger a ROS‐dependent systemic signal that alters the stomatal aperture in multiple systemic untreated leaves within minutes (Figs ).…”
mentioning
confidence: 97%
“…Multiple intracellular protein kinases induce phosphorylation of RBOHD's N-terminus at activating residues to ensure ROS production including CPKs, BIK1, and SIK1 [21][22][23] . RBOHD is also phosphorylated at activating residues by the receptor Doesn't Respond to Nucleotides 1 (DORN1) upon extracellular ATP perception 24 . While phosphorylation events that activate RBOHD are well characterized, our understanding of how ROS production mediated by NADPH oxidases is inhibited pre-and postpathogen recognition remains unclear.…”
mentioning
confidence: 99%
“…Mechanical stimulation-induced Ca 2+ and H + fluxes depend on the RECEPTOR-LIKE KINASE (RLK) FERONIA, which acts as a receptor for RAPID ALKALIZATION FACTOR (RALF) peptides (Haruta et al, 2014; Shih et al, 2014; Stegmann et al, 2017). Several RLKs, including the ATP receptor DOES NOT RESPOND TO NUCLEOTIDES 1 (DORN1) and PEP RECEPTORS (PEPRs), can induce Ca 2+ signals, apoplastic alkalization (coupled to cytosolic acidification), and ROS production (Qi et al, 2010; Choi et al, 2014; Ma et al, 2014; Seybold et al, 2014; Haruta et al, 2015; Chen et al, 2017; Kimura et al, 2017). The effect of DORN1 and PEPRs on anion efflux was observed in guard cells during stomatal closure (Chen et al, 2017; Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several RLKs, including the ATP receptor DOES NOT RESPOND TO NUCLEOTIDES 1 (DORN1) and PEP RECEPTORS (PEPRs), can induce Ca 2+ signals, apoplastic alkalization (coupled to cytosolic acidification), and ROS production (Qi et al, 2010; Choi et al, 2014; Ma et al, 2014; Seybold et al, 2014; Haruta et al, 2015; Chen et al, 2017; Kimura et al, 2017). The effect of DORN1 and PEPRs on anion efflux was observed in guard cells during stomatal closure (Chen et al, 2017; Zheng et al, 2018). Our analyses revealed that PEP1 induced a transient anion influx along the entire imaged root axis.…”
Section: Discussionmentioning
confidence: 99%